2023
DOI: 10.1021/acs.estlett.3c00505
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Covariation of Atmospheric O2 and Pollutants in an Industrial Metropolis by Explainable Machine Learning

Xiaoyue Liu,
Li Wang,
Jianping Huang
et al.

Abstract: In urban areas, atmospheric O 2 actively participates in the process of anthropogenic emissions and energy consumption. However, the covariation between atmospheric O 2 and the emitted pollutants has yet to be thoroughly explored. This study examines the covariations between atmospheric O 2 and pollutants in Lanzhou, a semi-arid industrial metropolis. A machine learning (ML)-based O 2 simulator coupled with a SHapley Additive exPlanation (SHAP) algorithm is established to explore and interpret their covariatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, no previous studies have reported such high deviations of ER atmos from ER forest , or ER atmos values higher than 2 for above forest canopy measurements as we found in Faassen et al (2023). Only Liu et al (2023b) found a difficult to explain nonlinear relationship between O 2 and other pollutants. While some differences between ER atmos and ER forest have been observed in previous studies, these differences typically fall within a range of 0.5 (Seibt et al, 2004;Ishidoya et al, 2015;Battle et al, 2019;Yan et al, 2023).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…To the best of our knowledge, no previous studies have reported such high deviations of ER atmos from ER forest , or ER atmos values higher than 2 for above forest canopy measurements as we found in Faassen et al (2023). Only Liu et al (2023b) found a difficult to explain nonlinear relationship between O 2 and other pollutants. While some differences between ER atmos and ER forest have been observed in previous studies, these differences typically fall within a range of 0.5 (Seibt et al, 2004;Ishidoya et al, 2015;Battle et al, 2019;Yan et al, 2023).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%